PENGARUH MONITORING CONTROL DAN KONDISI ADVERSE SELECTION TERHADAP ESKALASI KOMITMEN PENGAMBILAN KEPUTUSAN INVESTASI : Monitoring Control, Adverse Selection, Commitment Escalation - Ningsih, Sulistya (Fakultas Ekonomi Universitas Gresik, 2020)
This study aims to identify and analyze the effect of monitoring control and adverse selection on the escalation of commitment to investment decision making. This study used a factorial 2x2 Beetween subject experimental design with an instrument in the form of a case. Participants in this study were students of the accounting study program as a manager's proxy, with a purpose sampling technique, which had taken Management Accounting and Financial Management courses. There were 59 participants in this study. The analysis technique used was two ways ANOVA. The results showed that monitoring control and adverse selection had an effect on the escalation of investment decision-making commitment.